Contribution of Metacognitive Skills to Students' Conceptual Understanding and Problem-Solving Skills in Elementary School Teacher Education - Mumun Nurmilawati; Punadji Setyosari; Mohamad Amin; Dedi Kuswandi; Sulistiono Sulistiono; Agus Muji Santoso; Mohd Hanafi Mohd Yasin (Journal of Innovation in Educational and Cultural Research, 2026)
Metacognitive skills constitute one's cognitive awareness or affective experience that comes along with intellectual efforts. It represents one's awareness and knowledge about his/her own cognitive skills. Metacognitive skills affect one's conceptual understanding and problem-solving skills. Empirical researchanalyzinghow metacognitive skills specifically contribute to conceptual understanding and problem-solving skills through free inquiry-based learning is still lacking. This study aimed to examine how metacognitive skills contribute to individuals' conceptual understanding and problem-solving using free, inquiry-based learning strategies. To this end, a descriptive correlational study was applied.The independent variable in this study was metacognitive skills, and the dependent variables were conceptual understanding and problem-solving abilities. Thirty-five students from the Elementary School Teacher Education Department of Universitas Nusantara PGRI Kediri participated. Data wereanalyzedusing linear regression analysis. The result showed that metacognitive skills contribute 48.9% to students' conceptual understanding, higher than their contribution to problem-solving skills (i.e., 30.7%).These findings demonstrate the important role of metacognitive skills in shaping effective teacher preparation and fostering reflective and independent learners. This study provides empirical evidence for integrating metacognitive skill development into inquiry-based teacher education programs to enhance conceptual and problem-solving competencies.